Gambaran Resiliensi dan Kebersyukuran Caregiver pada Anak yang Mengalami Down Syndrome di Wilayah Kota Semarang - Megana Lova Wijaya; Laura Khattrine Noviyanti; Sri Hartini (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Down syndrome refers to intelligence disability due to neural development disorders, These problems lead to interrupted social, academic, and occupational problems. Objective: This research describes the resilience and gratefulness of caregivers of children suffering from Down syndrome in Semarang. Method: This research is quantitative. Sample: the samples were 30 respondents taken with total sampling. The applied test was a statistic descriptive test. Research results: The applied statistic test found 22 caregivers had very high resilience while 18 caregivers had high resilience in the children suffering from Down syndrome. Thirty caregivers had high gratefulness for children suffering from Down syndrome in Semarang regency. Suggestion: the researcher expects future researchers to develop resilience and gratefulness of caregivers for children suffering from Down syndrome.